Tourism Transformation and the Limits of Local Fiscal Capture: Evidence from Bangka Belitung - Muhamad Mufti Arkan; Devi Valeriani; Annisa Deni Istina; Andi Kurniawan Karta Negara (Equity: Jurnal Ekonomi, 2026)
This study investigates whether tourism-led economic transformation has generated employment and strengthened local fiscal capacity in Bangka Belitung Province, Indonesia. This issue is important because the province has historically relied on tin mining, while tourism has increasingly been positioned as an alternative pathway for post-mining development. Using panel data from seven regencies and municipalities during 2011–2025, the study applies descriptive analysis, fixed-effects estimation, first-difference models, and a dynamic difference-in-differences/event-study approach. Tourism transformation is proxied by the share of tourism-related gross regional domestic product, while local own-source revenue and employment are used as the main outcome variables. The findings show that tourism transformation has not consistently increased local own-source revenue or employment. Event-study estimates indicate a positive early employment response, but no corresponding improvement in fiscal capacity. These results suggest that tourism creates labor-market benefits more rapidly than local fiscal gains, revealing a weak mechanism of local revenue capture from tourism activity. The study underscores the importance of strengthening tourism fiscal governance, business formalization, digital tax administration, and linkages between tourism and local micro, small, and medium enterprises.